Alternative treatment to corticosteroids in steroid sensitive idiopathic nephrotic syndrome. Issue 6 (December 1994) - Neuhaus, T J; Fay, J; Dillon, M J; Trompeter, R S; Barratt, T M
Abstract : A review was undertaken of the use of alternative immunosuppressive treatment in addition to corticosteroids in a cohort of 429 children with steroid sensitive nephrotic syndrome (SSNS) treated between 1980 and 1994. Two hundred and twenty two children (52%) received at least one course of alternative treatment, 98 (23%) two, and 43 (10%) three. Cyclophosphamide was administered to 196 children (46%); in 181 it was the first course of alternative treatment and in 104 (57%) of those it was also the last ('final course'). Levamisole was given to 56 children (13%) and cyclosporin to 53 (12%). Fifteen children in whom cyclosporin failed were treated with chlorambucil. A few patients received azathioprine or vincristine. Ten children developed secondary steroid resistance, of whom five progressed to chronic renal failure. Acute complications included reversible renal failure, septicaemia, peritonitis, convulsions, and cerebral thrombosis. There were three deaths. It is concluded that half of the referred children with SSNS were deemed to require at least one course of alternative immunosuppressive treatment, and that side effects of the treatment and complications of SSNS are infrequent but occasionally fatal.